IMPACT OF HEAVY METALS ON HEXOKINASE ISOFORMS: AN IN SILICO STUDY - Ellen Ayuningtyas Pratidina; Eko Suhartono; Bambang Setiawan (Fakultas Kedokteran Universitas Lambung Mangkurat, 2022)
Abstract: Coal mining activities in South Kalimantan produce waste that is very dangerous if not processed wisely. Coal waste produces heavy metals cadmium and mercury that can pollute the environment. Heavy metals that enter the human body will cause negative impacts in the field of health such as the disruption of the glycolysis process in humans. The purpose of this study was determine the interaction of heavy metals which is cadmium and mercury against hexokinase enzymes using hexokinase enzymes type I, II, III with PDB ID : 4F9O, 2NZT, 3HM8 taken from Protein Data Bank and using the molecular docking website MIB: Metal Ion Binding Site Prediction and Docking server. Docking results will be visualized using chimera app version 1.15. Molecular docking of the heavy metals cadmium and mercury can interact with all three types of hexokinase enzymes. Cadmium metal ions bind hydrophobicly to amino acid residues of hexokinase enzymes type I, II, and III, while mercury metal ions bind covalently coordinate with amino acid residues of hexokinase enzymes type I and III. Mercury metal ions bind more strongly than cadmium metal ions. Of the three types of hexokinase enzymes, mercury metal ions bind most strongly with hexokinase enzyme type II because mercury ions bind to the active site of the three amino acid residues of hexokinase enzymes type II.Keywords: Cadmium ; hexokinase enzyme ; mercury ; molecular docking